Analisis Kepuasan Pengguna Aplikasi Wattpad Dengan Menggunakan Metode End User Computing Satisfaction (EUCS) - Yohana Kristiani Tampubolon; Agus Nugroho; Feri Pebrianto (GLOBAL SCIENTS PUBLISHER, 2026)
The purpose of this study is to use the End User Computing Happiness (EUCS) approach to assess user satisfaction with the Wattpad application in Jambi City. The five main components of this approach are content, accuracy, format, timeliness, and ease of use and user satisfaction are used to evaluate end-user satisfaction. A questionnaire was used to obtain data from Wattpad users who are active users or have previously used the application. According to the research findings, accuracy, appearance, and ease of use have the greatest influence on customer satisfaction. However, in order to provide the best possible user experience, Content and Timeliness still need improvement. Through this analysis, application developers and marketing strategies can be improved to optimize features and services, so as to increase user satisfaction and loyalty in Jambi City.